A directed collaboration network for exploring the order of scientific collaboration. Issue 4 (November 2022) - Zhai, Li; Yan, Xiangbin
Highlights: A directed collaboration network (DCN) was proposed for exploring the order of collaboration. The DCN is established based on the signature order. The theoretical properties of the DCN are analyzed and two measures of diversity of collaboration order are constructed. The DCN enriches scientific collaboration research tools and expands the existing collaboration networks. Abstract: The rapid growth of scientific collaboration and its significant role in promoting academic productivity has attracted increasing scientific community attention. The collaboration networks have become a powerful tool for studying scientific collaboration. Collaboration networks commonly used in research treat the collaborators as equal in status. However, the roles and contributions of different collaborators are not the same. Those differences are usually reflected through the signature order of academic achievements. This paper expands the construction of scientific collaboration networks with a directed collaboration network (DCN) to describe the different roles of collaborators and the connectivity and strength of collaborations. We analyzed the theoretical properties of the DCN and constructed evaluation indexes describing the diversity of collaboration order. Based on a case study of published papers in the business field, we discuss the value of the DCN in the characterization and evaluation of scientific collaboration and compare the DCN with two other collaboration networks. We found that the DCN provides a powerful new approach for investigating collaboration laws and patterns.